Perkembangan Pandai Besi Di Nagari Sungai Pua (1998-2020) - Afrizal Afrizal; Rusdi Rusdi (Jurnal Kronologi, 2023)
This research examines the Development of Blacksmiths in Nagari Sungai Pua (1998-2020). The problem is formulated as follows: "How is the development of blacksmith craftsmen in Nagari Sungai Pua and how is the social and economic life of blacksmith craftsmen in Nagari Sungai Pua." This research aims to examine the development of blacksmith craftsmen in Nagari Sungai Pua and to examine the social and economic life of blacksmith craftsmen in Nagari Sungai Pua. The method used in this study is the historical method with four stages of historical research methods: (1) heuristics, namely an activity to search for and collect traces of the past or historical sources related to the theme to be studied. (2) Source criticism which includes external criticism and internal criticism. (3) Interpretation, namely the data obtained is analyzed. (4) Historiography, namely historical writing in the form of scientific writing. Nagari Sungai Pua from 1998-2020 experienced a decline. caused by the high capital spent by blacksmith craftsmen due to expensive raw materials, high competition with foreign products and the low interest of the younger generation to continue blacksmithing in Nagari Sungai Pua, this affects the socio-economic community of Nagari Sungai Pua.The presence of blacksmith craftsmen in Nagari Sungai Pua has an impact on the socio-economic life of the craftsmen in Nagari Sungai Pua. Because blacksmiths do not only work as blacksmiths, blacksmiths in Nagari Sungai Pua also do agriculture. By carrying out blacksmithing and farming activities, the craftsmen can get income that can help the family econom. Keywords: Blacksmith, Development, Socioeconomic